2005
DOI: 10.1016/s1472-6483(10)60939-x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of oocyte population in the fetal ovary: primordial germ cell proliferation and oocyte programmed cell death

Abstract: Strict control of cell proliferation and cell loss is essential for the coordinated functions of different cell populations in complex multicellular organisms. Oogenesis is characterized by a first phase occurring during embryo-fetal life and in common with spermatogenesis, during which mitotic proliferation of the germline stem cells, the primordial germ cells (PGC), prevails over germ cell death. The result is the formation of a relatively high number of germ cells depending on the species, ready to enter se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(81 citation statements)
references
References 74 publications
1
76
1
3
Order By: Relevance
“…In all the mammalian species studied, there is an oversupply of germ cells within the late fetal ovary (Coucouvanis et al 1993, Vaskivuo et al 2001, Vaskivuo & Tapanainen 2002. Depending on the species, many oocytes are eliminated by apoptosis prior to and at the time of birth (Ratts et al 1995, Reynaud & Driancourt 2000, Shirota et al 2003, De Felici 2004, and those that remain in the neonatal mouse ovary acquire and are surrounded by granulosa cells, establishing a pool of diplotene-arrested oocytes identified as primordial follicles (Pedersen 1969, Peters 1969. The enclosure of oocytes by granulosa cells during the first postnatal week of ovarian development exhibits temporal and spatial heterogeneity within the ovary, since larger diplotene-arrested oocytes that form primordial follicles first appear in the deep cortex and medulla (Byskov & Nielson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In all the mammalian species studied, there is an oversupply of germ cells within the late fetal ovary (Coucouvanis et al 1993, Vaskivuo et al 2001, Vaskivuo & Tapanainen 2002. Depending on the species, many oocytes are eliminated by apoptosis prior to and at the time of birth (Ratts et al 1995, Reynaud & Driancourt 2000, Shirota et al 2003, De Felici 2004, and those that remain in the neonatal mouse ovary acquire and are surrounded by granulosa cells, establishing a pool of diplotene-arrested oocytes identified as primordial follicles (Pedersen 1969, Peters 1969. The enclosure of oocytes by granulosa cells during the first postnatal week of ovarian development exhibits temporal and spatial heterogeneity within the ovary, since larger diplotene-arrested oocytes that form primordial follicles first appear in the deep cortex and medulla (Byskov & Nielson 2003).…”
Section: Discussionmentioning
confidence: 99%
“…LIF has been widely studied as a media additive important for the maintenance of ES cells in a self-renewing, undifferentiated state [21][22][23][24]. However, based on several reports demonstrating the importance of LIF not only in the survival and self-renewal of PGCs [25][26][27]44], but also in the maturation of oocytes and ovarian follicles [26,28,31,45], we decided to study its role in the formation of germ cells from ES cells in vitro. We found that LIF, when added to the media of ES cells differentiating in the absence of a MEF monolayer, significantly increased not only the number of eGFP-positive oocyte-like cells, but also the expression of oocyte specific genes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…We first focused our attention on the media additive LIF. While LIF has been extensively studied as an important factor in stem cell self-renewal [21][22][23][24], several studies have reported the importance of LIF in the development of primordial and primary follicles of the ovary and have determined LIF is necessary for oocyte maturation [25][26][27][28][29]. PGK12.1 XX ES cells transfected with the Gdf9/eGFP were grown on a MEF monolayer in the presence of LIF for two days.…”
Section: Effects Of Lif On Gdf9 Promoter Activity and Gene Expressionmentioning
confidence: 99%
“…Once in the gonadal anlage, the primordial germ cells migrate centrally forming primitive sex cords after which they cease motility and are called oogonia. However, these cells proliferate extensively during their migration and continue to do so as oogonia after colonization of the gonads (De Felici et al 2005). The oogonia then begin forming nests, beginning at E10.5 in mice, and are connected by intercellular bridges.…”
Section: Establishment Of the Ovarian Pool Of Primordial Folliclesmentioning
confidence: 99%